Fecal Microbiota Transplantation Modulates Renal Phenotype in the Humanized Mouse Model of IgA Nephropathy - Lauriero, Gabriella; Abbad, Lilia; Vacca, Mirco; Celano, Giuseppe; Chemouny, Jonathan M.; Calasso, Maria; Berthelot, Laureline; Gesualdo, Loreto; De Angelis, Maria; Monteiro, Renato C. (Frontiers in Immunology, 2021)
Immunoglobulin A nephropathy (IgAN) is the most common primary glomerulonephritis. Several observations suggest that gut microbiota could be implicated in IgAN pathophysiology. Aiming at exploring whether microbiota modulation is able to influence disease outcome, we performed fecal microbiota transplantation (FMT) from healthy controls (HC-sbjs), non-progressor (NP-pts) and progressor (P-pts) IgAN patients to antibiotic-treated humanized IgAN mice (α1KI-CD89Tg), by oral gavage. FMT was able to modulate renal phenotype and inflammation. On one hand, the microbiota from P-pts was able to induce an increase of serum BAFF and galactose deficient-IgA1 levels and a decrease of CD89 cell surface expression on blood CD11b+ cells which was associated with soluble CD89 and IgA1 mesangial deposits. On the other hand, the microbiota from HC-sbjs was able to induce a reduction of albuminuria immediately after gavage, an increased cell surface expression of CD89 on blood CD11b+ cells and a decreased expression of KC chemokine in kidney. Higher serum BAFF levels were found in mice subjected to FMT from IgAN patients. The main bacterial phyla composition and volatile organic compounds profile significantly differed in mouse gut microbiota. Microbiota modulation by FMT influence IgAN phenotype opening new avenues for therapeutic approaches in IgAN.